2009
DOI: 10.1016/j.neuron.2008.11.013
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Microtubules Regulate Dendritic Spine Morphology and Synaptic Plasticity

Abstract: Dendritic spines are the major sites of excitatory synaptic input, and their morphological changes have been linked to learning and memory processes. Here, we report that growing microtubule plus ends decorated by the microtubule tip-tracking protein EB3 enter spines and can modulate spine morphology. We describe p140Cap/SNIP, a regulator of Src tyrosine kinase, as an EB3 interacting partner that is predominantly localized to spines and enriched in the postsynaptic density. Inhibition of microtubule dynamics, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

41
655
2
4

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 575 publications
(713 citation statements)
references
References 59 publications
(107 reference statements)
41
655
2
4
Order By: Relevance
“…There is now considerable evidence that microtubule invasion of dendritic spines underlies morphological and physiological changes associated with memory formation including F-actin stabilization, spine maturation and enlargement of the PSD . Consistent with these findings, shRNA-mediated knock-down of EB3 reduces spine enlargement (Gu et al 2008;Jaworski et al 2009). An early event in dendritic spine enlargement associated with increased synaptic strength is an enlargement of the PSD and a concomitant increase in PSD-95, the major scaffolding protein of the PSD.…”
Section: Activity-driven Microtubule Capture and Insertion Into Dendrsupporting
confidence: 62%
See 2 more Smart Citations
“…There is now considerable evidence that microtubule invasion of dendritic spines underlies morphological and physiological changes associated with memory formation including F-actin stabilization, spine maturation and enlargement of the PSD . Consistent with these findings, shRNA-mediated knock-down of EB3 reduces spine enlargement (Gu et al 2008;Jaworski et al 2009). An early event in dendritic spine enlargement associated with increased synaptic strength is an enlargement of the PSD and a concomitant increase in PSD-95, the major scaffolding protein of the PSD.…”
Section: Activity-driven Microtubule Capture and Insertion Into Dendrsupporting
confidence: 62%
“…Dynamic microtubules in dendrite shafts can transiently enter dendritic spines by polymerizing from their plus-ends, the end at which tubulin assembly occurs preferentially (Gu et al 2008;Hu et al 2008;Jaworski et al 2009;Wagner et al, 2011;Merriam et al, 2013). The frequency of invasion is low, with approximately 1% of dendritic protrusions containing a microtubule at any one time (Hu et al 2008) and the dwell time is in the order of minutes but, importantly, dwell time and the frequency of invasion are enhanced by pharmacological interventions that mimic LTP (Gu et al 2008, Hu et al 2008Mitsuyama et al 2008;Jaworski et al 2009;Merriam et al 2011) and supressed by eliciting LTD (Kapitein et al 2011).…”
Section: Activity-driven Microtubule Capture and Insertion Into Dendrmentioning
confidence: 99%
See 1 more Smart Citation
“…The rationale for including p140Cap in the assay results from our previous demonstration that acute downregulation of SNAP-25 impairs spines morphogenesis through p140Cap, 23 a synaptic protein involved in Src-kinase regulation and microtubules organization inside the spine. 41 The well-characterized protein/protein interaction (Figure 5c). Results indicated that SNAP-25 and PSD-95 do not interact directly, whereas p140Cap specifically interacts with PSD-95 (Figure 5c).…”
Section: Resultsmentioning
confidence: 99%
“…p140CAP has been shown to co-localize with actin stress fibres and cortical actin and to associate with proteins involved in actin cytoskeleton dynamics, such as p130CAS, SRC, VINEXIN and CORTACTIN 41,42,119 . These findings along with the presence of a putative actin-binding domain in p140CAP (Figure 1), suggest that this adaptor could be directly or indirectly involved in actin filaments assembly.…”
Section: Migration and Invasion P140cap Decreases The Ability Of Brementioning
confidence: 99%